Imbalanced expression of polycistronic miRNA in acute myeloid leukemia - Kotaki, Ryutaro; Higuchi, Hiroshi; Ogiya, Daisuke; Katahira, Yasuhiro; Kurosaki, Natsumi; Yukihira, Naoko; Ogata, Jun; Yamamoto, Haruna; Mohamad Alba, Syakira; Azhim, Azran; Kitajima, Tatsuo; Inoue, Shigeaki; et al. (Springer International Publishing AG, 2017)
miR-1 and miR-133 are clustered on the same chromosomal loci and are transcribed together as a single transcript that is positively regulated by ecotropic virus integration site-1 (EVI1). Previously, we described how miR-133 has anti-tumorigenic potential through repression of EVI1 expression. It has also been reported that miR-1 is oncogenic in the case of acute myeloid leukemia (AML). Here, we show that expression of miR-1 and miR-133, which have distinct functions, is differentially regulated between AML cell lines. Interestingly, the expression of miR-1 and EVI1, which binds to the promoter of the miR-1/miR-133 cluster, is correlative. The expression levels of TDP-43, an RNA-binding protein that has been reported to increase the expression, but inhibits the activity, of miR-1, were not correlated with expression levels of miR-1 in AML cells. Taken together, our observations raise the possibility that the balance of polycistronic miRNAs is regulated post-transcriptionally in a hierarchical manner possibly involving EVI1,suggesting that the deregulation of this balance may play some role in AML cells with high EVI1 expression.